De Negatione: What Does It Mean to Say No? - Magun, Artemy (Stasis, 2013)
The article deals with the history of the concept of negativity in western thought. While reproducing the classical approaches in all essential details, the text exceeds the encyclopedia format of encyclopedia since it seeks to describe and systematize the main features of negation as a logical and linguistic operator: its asymmetry with affirmation; its incompletion and infinity; its latency in alternation with hyperbolic repetition. Further, in its reliance on Aristotle, Kant, and Hegel, the article emphasizes the crucial role of inversion (correlative, contrary or real opposition) as a scheme and practical realization of negation. The history of negation is then anchored in the socio-political context, where it is shown to be a necessary form of subjectivization in the late modernity, with its excess of inescapable being.